ІНТЕГРАЛЬНЕ ПРЕДСТАВЛЕННЯ РОЗВ’ЯЗАННЯ ЗМІШАНИХ ПАРАБОЛІЧНИХ ЗАДАЧ З М'ЯКОЮ МЕЖЕЮ НА ПОЛЯРНІЙ ОСІ - Konet, Ivan Mykhajlovych; Pylypyuk, Tatiana Mykhajlivna (Кам'янець-Подільський національний університет імені Івана Огієнка, 2013)
By means of method of hybrid integral transform of Legendre-Bessel-Legendre type with the spectral parameter the integral representation of exact analytical solution of mixed problem for the system of equations of parabolic type in the piece-homogeneous polar axis with soft limits is obtained. Modeling of evolutionary process is made by the method of hybrid differential Legendre-Bessel-Legendre operator.